Pengaruh edukasi gizi menggunakan e-diary terhadap pengetahuan, sikap, dan persepsi perilaku pada remaja putri - Halimatussa'diah, Della Martha; Tambunan, Maria; Sitoayu, Laras; Gifari, Nazhif (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: The higher the level of knowledge, the more likely adolescents are to have better alternatives and behave positively. The results of a preliminary study stated that the knowledge, attitudes, and behavioral perceptions of adolescent girls are still in the poor category on average. The data shows that the proportion of malnutrition in adolescent girls is still in the high prevalence category. Therefore, nutrition education is needed to support and improve the knowledge, attitudes, and behavioral perceptions of adolescent girls.Objectives: To find out the effect of providing education on balanced nutrition guidelines using e-diaries for adolescent girls on the knowledge, attitudes and behavioral perceptions of adolescent girls at Poris Indah High School, Tangerang City.Methods: This study uses the Pre Experiment Design method with the One Group Pre test-Post test Non Control Group Design approach. The number of samples is 33 female adolescents taken using a purposive sampling technique. This study was conducted for 18 days at Poris Indah High School, namely in August - September 2023. Female adolescents will be given a pre-test, then given nutritional education using e-diary media, then a post-test will be carried out, for the behavioral perception variable it will be carried out 18 days after the education. Data analysis using the Wilcoxon test.Results: The results showed an increase in knowledge, attitudes, and behavioral perceptions in adolescent girls after being given nutrition education using the adolescent girl e-diary media (p = 0,0001). The results of the pre-post test of knowledge, attitudes, and behavioral perceptions were 56,67 and 81,21, 62,95 and 95,68, 52,73 and 72,42 respectively.Conclusion: There is an influence of providing balanced nutrition guidelines education using e-diary media for female adolescents on the knowledge, attitudes, and behavioral perceptions of female adolescents at SMA Poris Indah, Tangerang City.